A single-component photorheological fluid with light-responsive viscosity. Issue 11 (12th March 2020) - Kelly, Elaine A.; Willis-Fox, Niamh; Houston, Judith E.; Blayo, Camille; Divitini, Giorgio; Cowieson, Nathan; Daly, Ronan; Evans, Rachel C.
Abstract : A single-component photorheological fluid comprised of a neutral photosurfactant in water can reversibly switch its viscosity four orders of magnitude, between high and low viscosity states, depending on the wavelength of light used. Abstract : Viscoelastic fluids whose rheological properties are tunable with light have the potential to deliver significant impact in fields relying on a change in flow behavior, such as in-use tuning of combined efficient heat-transfer and drag-reduction agents, microfluidic flow and controlled encapsulation and release. However, simple, single-component systems must be developed to allow integration with these applications. Here, we report a single-component viscoelastic fluid, capable of a dramatic light-sensitive rheological response, from a neutral azobenzene photosurfactant, 4-hexyl-4′butyloxymonotetraethylene glycol (C6 AzoOC4 E4 ) in water. From cryo-transmission electron microscopy (TEM), small-angle X-ray scattering (SAXS) and rheology measurements, we observe that the photosurfactant forms an entangled network of wormlike micelles in water, with a high viscosity (28 Pa s) and viscoelastic behaviour. UV irradiation of the surfactant solution creates a less dense micellar network, with some vesicle formation. As a result, the solution viscosity is reduced by four orders of magnitude (to 1.2 × 10 −3 Pa s). This process is reversible and the high and low viscosity states can be cycled several times, through alternating UV and blue light irradiation.